Gender and leadership aspiration: the impact of organizational identification. Issue 8 (8th September 2017) - Fritz, Claudia; van Knippenberg, Daan
Abstract : Purpose: Although nowadays more women occupy leadership roles, they still are a minority. Because aspiration is a precursor of advancement, examining conditions fostering female leadership aspiration is important. A neglected perspective is the impact of organizational identification. Identification can be argued to foster leadership aspiration because the essence of leadership is the pursuit of collective interests, and identification motivates such pursuits. The paper aims to discuss these issues. Design/methodology/approach: A cross-sectional survey design with an n =400 fulltime employed men and women, working for various organizations was selected. Findings: The initial prediction was that identification is more important to women's leadership aspiration to the extent that gender is associated with communal orientation, because women tend to have stronger communal orientation with associated greater affiliation needs, and organizational identification can be expected to cater to those needs. The communal orientation by organizational identification interactive influence on leadership aspiration was supported. Also, the indirect effect of gender on leadership aspiration via this interactive influence of communal orientation and organizational identification was supported. Research limitations/implications: Due to the selected survey approach the data are correlational and as a result no reference to matters of causality can be made. Thus (field) experimental data is needed to confirm these findings. Practical implications: Within the paper the discussion focuses on the importance of creating an environment that is more conducive to organizational identification and as such speaks to the communal orientation – being more pronounced among women – to act in favor of the organization by aspiring leadership positions. Originality/value: The presented results depict an important step toward understanding how organizational identification and communal orientation interact and how they interact with women's leadership aspiration.